DESAIN SPATULA ERGONOMIS MENGGUNAKAN PENDEKATAN MODEL KANO - Rustam Sidiq; Hari Purnomo (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Occupational accidents often occur in the workplace kitchens, one of which was during the times of frying. During frying one of the tools that cause accidents are prone spatula, then from it in carefully designed spatula which can reduce the risk of injury is based on the experience of the spatula by the user. Kano on the method used to determine the level of user satisfaction to the user experience in the use of a product. From other research on get 4 attribute that affects the user's satisfaction spatula users are safe from the stepping oil, spatula attributes not easily conduct heat, attributes spatula material is non-flammable and attributes spatula comfortable grip. Then make a proposal spatula design for the user, that is spatula design with hand protector, use of raw materials falcata wood combined with stainlees steel and approach anthropometric calculations to determine the amount of the dimensions of the proposed design spatula. So with spatula design in the proposal it is expected spatula able to provide security and comfort when in use by the user.